THE QUESTION OF THE CONSERVATION OF WILD RELATIVES OF CULTIVATED PLANTS IN THE TERRITORY OF LENINGRAD, NOVGOROD AND PSKOV REGIONS - L. J. Shipilina (Труды по прикладной ботанике, генетике и селекции)
Improved method for the selection of taxa for the regional red list, developed scoring system for inclusion of taxa on the red list CWR and preserve them in situ in the respective regions.